You would need to remove (-2, 1)
Answer: Function g reflected function f across the x-axis.
For function g, as x approaches negative infinity, g(x) approaches negative infinity.
Function f is symmetrical about the point (4,6).
I don’t know what exactly you are trying to ask? But this equation would be an example of exponential growth.
Answer:
11 and 5/16
Hope this answers your question
Answer:
q= -ck+dp/
-k+d
Step-by-step explanation:
Step 1:
Multiply both sides by p.
dp=ck−kq+pq
Step 2:
Flip the equation.
ck−kq+pq=dp
Step 3:
Add -ck to both sides.
−kq+pq=−ck+dp
Step 4:
Factor out variable q.
q(−k+p)=−ck+dp
Step 5:
Divide both sides by -k+p.
q= -ck+dp/
-k+d
Sorry if it's all letters and u needed numbers.